Non-human Primate Models to Explore the Adaptive Mechanisms After Stroke - Higo, Noriyuki (Frontiers in Systems Neuroscience, 2021)
The brain has the ability to reconstruct neural structures and functions to compensate for the brain damage caused by stroke. Animal studies in which artificial damage was induced in the brain have contributed to the current understanding of the neural mechanisms underlying functional recovery. Here, I have highlighted recent advances in nonhuman primate models using primate species such as macaques and marmosets, most of which have been developed to study the mechanisms underlying the recovery of motor functions after stroke. Cortical lesion models have been used to investigate motor recovery after damage to the cortical areas involved in movements of specific body parts. Models of focal stroke at the posterior internal capsule have also been developed to bridge the gap between the knowledge obtained by cortical damage models and the development of intervention strategies, because the severity and outcome of motor deficits depends on the degree of damage to the region. This mini-review will also introduce other stroke models designed to study the plastic changes associated with development and recovery from cognitive and sensory impairments. Although further validation and careful interpretation are required, considering the differences between nonhuman primate brains and human brains, studies using brain-damaged nonhuman primates offer promise for improving translational outcomes.